Mark Logic - Isaacs, Andrew M.; Norman, Emily (London : SAGE Publications Ltd, 2017)
The Mark Logic case study takes place in 2004 when Paul Pedersen, founder of Mark Logic, is at a crossroads about which business strategy to pursue. Mark Logic was founded by Pedersen, the former Lead Software Architect for Google, and Chris Linblad, the Principal Engineer and creator of the search engine at Ultraseek. In founding Mark Logic, Pedersen and Linblad had the vision of developing a product that would apply the same concepts of a traditional web search engine to quickly and efficiently locate and manage enterprise content such as PDF documents, textbooks, newspaper articles, tabular reference data, technical manuals, company financial reports, clinic trial data, and other information that is not easily accessible using simple keyword searches. By adapting web search technology to be used for identifying specific information within documents and other content, Pederson and Linblad hoped to create a technology that could integrate all of a companys key content into a searchable database. By 2004, Mark Logic was serving six clients that included two of the worlds top five publishing companies, a US Air Force research enter, the Alberta provincial government, the Cedars-Sinai medical research center, and the University of Virginia Press. Despite Mark Logics early success, Pederson now was at a crossroads in terms of strategy. Specifically, he was considering three key strategies: a horizontal strategy, a vertical strategy, and an original equipment manufacturer (OEM) partnership strategy. The horizontal strategy would call for developing specific applications that would appeal to customers in various industries. For example, Mark Logic could produce a call center application, a project management application, and a contract management application. The vertical strategy would call for developing generalized applications for specific industries. For example, Mark Logic could develop an application for pharmaceutical companies that allow them to analyze clini
Originally published in Isaacs, A. M., & Norman, E. (2004). Mark Logic. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mark Logic; Strategic planning -- Case studies; Business planning -- Case studies; Computer software -- Case studies